Linguoculturology as the New Branch of Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The following article describes the facts concerning the formation and characteristics of linguoculture, as well as the viewpoints of many specialists on the field and the way it has developed within Uzbek linguistics.